Recent advances in hidradenitis suppurativa: Role of race, genetics, and immunology - Vellaichamy, Gautham; Amin, Anya T.; Dimitrion, Peter; Hamzavi, Zaakir; Zhou, Li; Adrianto, Indra; Mi, Qing-Sheng (Frontiers in Genetics, 2022)
Hidradenitis suppurativa (HS) is a multifactorial chronic skin disease characterized by inflammation around the hair follicles commonly affecting intertriginous areas. The underlying pathogenesis of HS and its molecular mechanisms are largely understudied. Genetic studies in families have identified variants within the γ-secretase complex associated with HS; however, no definitive genotype-phenotype correlations have been made. The lack of knowledge regarding the intersection of genetics, immunology and environmental risk factors is a major obstacle to improving treatment for patients with HS. This article provides an overview of the role of race, genetics, and immunology in HS to provide insight into the multiple factors influencing the pathophysiology of HS.